Host Genetics in Granuloma Formation: Human-Like Lung Pathology in Mice with Reciprocal Genetic Susceptibility to M. tuberculosis and M. avium - Kondratieva, Elena (Public Library of Science, 2010)

(untitled)
Development of lung granulomata is a hallmark of infections caused by virulent mycobacteria, reflecting both protective host response that restricts infection spreading and inflammatory pathology. The role of host genetics in granuloma formation is not well defined. Earlier we have shown that mice of the I/St strain are extremely susceptible to Mycobacterium tuberculosis but resistant to M. avium infection, whereas B6 mice show a reversed pattern of susceptibility. Here, by directly comparing: (i) characteristics of susceptibility to two infections in vivo; (ii) architecture of lung granulomata assessed by immune staining; and (iii) expression of genes encoding regulatory factors of neutrophil influx in the lung tissue, we demonstrate that genetic susceptibility of the host largely determines the pattern of lung pathology. Necrotizing granuloma surrounded by hypoxic zones, as well as a massive neutrophil influx, develop in the lungs of M. avium-infected B6 mice and in the lungs of M. tuberculosis-infected I/St mice, but not in the lungs of corresponding genetically resistant counterparts. The mirror-type lung tissue responses to two virulent mycobacteria indicate that the level of genetic susceptibility of the host to a given mycobacterial species largely determines characteristics of pathology, and directly demonstrate the importance of host genetics in pathogenesis.